2011
DOI: 10.1002/aoc.1790
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, anti‐inflammatory and analgesic activity of transition metal complexes of 3‐[1‐(2‐hydroxyphenyl) ethylideamino]‐2‐phenyl‐3,4‐dihydroquinazolin‐4(3H)‐one

Abstract: A new quinazolinone derivative, 3-[1-(2-hydroxyphenyl)ethylideamino]-2-phenyl-3,4-dihydroquinazolin-4(3H)-one (LH) wassynthesized by the condensation of 2-hydroxyacetophenone-2-aminobenzoylhydrazone and benzaldehyde. The cyclization to form 1,2-dihydroquinazolinone was confirmed by IR, 1D and 2D HETCOR studies. Coordination compounds of Co(II), Ni(II), Cu(II) and Zn(II) of LH were synthesized and characterized using various physico-chemical studies like stoichiometric, conductivity, magnetic moment measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The chemical structures of a novel bis‐Schiff base ligand and its mononuclear metal complexes were characterized using various physicochemical techniques. The present study revealed an octahedral geometry around the M(II)/M(III) complexes as indicated from diffuse reflectance and magnetic moment measurements . IR spectra revealed that the bis‐Schiff base ligand acts as a tetradentate ligand and its manner of coordination is through the nitrogen atoms of the azomethine (CH═N) and etheric O groups.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The chemical structures of a novel bis‐Schiff base ligand and its mononuclear metal complexes were characterized using various physicochemical techniques. The present study revealed an octahedral geometry around the M(II)/M(III) complexes as indicated from diffuse reflectance and magnetic moment measurements . IR spectra revealed that the bis‐Schiff base ligand acts as a tetradentate ligand and its manner of coordination is through the nitrogen atoms of the azomethine (CH═N) and etheric O groups.…”
Section: Discussionmentioning
confidence: 51%
“…From the data listed in Table , it was found that the Cu(II) complex had moderate inhibitory activity (28 and 29 mm) for E. coli and P. vulgaris , respectively. On the other hand, it registered high MIC 50 (>100 mg ml −1 ) for both microorganisms . But the Mn(II) complex has poorer inhibitory activity, where the diameters of the inhibition zone are 24 and 22 mm for E. coli and P. vulgaris , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The 1H‐NMR spectra of the synthesized Schiff‐base ligand revealed a characteristic signal at 9.98 ppm (s, 1H), which is attributable to the phenolic (–OH) proton (Figure S1); however, this signal is absent in the spectrum of its Ni(II) and zinc(II) complexes (Figure S3). This indicates that following deprotonation, the phenolic group (–OH) is coordinated with the metal ions 51 . In the Schiff‐base ligand, the distinctive signal of the azomethine proton (–CH═N) occurred at 8.97 ppm (s, 1H) (Figure S1).…”
Section: Resultsmentioning
confidence: 98%
“…The studies show when Schiff base ligands bind to metal ions, their antimicrobial and anticancer activities will be enhanced [10][11][12][13]. Schiff base complexes have been attracted many attention due to their good antimicrobial, antibacterial, antifungal, antiviral, antimycobacterial, anti-flammatory, analgesic, antitubercular, and antioxidant activities [14][15][16][17][18][19]. Furthermore, the interaction of these complexes with DNA has gained much attention due to their potentials as new therapeutic agents [20].…”
Section: Introductionmentioning
confidence: 99%